Development Of Larvae Rainbow Fish Boesemani (Melanotaenia boesemani): Phase Depreciation of Yellow Egg, Forming Eyes and Opening of Mouth - Dewi Elfidasari; Frenzysca Yuliani; Tutik Kadarini; Siti Zuhriyyah Musthofa (Universitas Al Azhar Indonesia, 2017)
Abstract – One of the factors that caused larval mortality is the availability of food which is not in accordance with the mouth opening. At the same time the larvae require considerable energy to the development of organs. The Completeness of organs used in feed searching as the eyes is also becoming important. The larvae use eyes to see the feed material in their surrounding waters. This study aimed to measure the volume of egg yolk, eye diameter and wide mouth opening during larval development rainbow fish boesemani (Melanotaenia boesemani). The stages of the research include larval maintenance, depreciation egg yolk observations, calculate the size of the increase in larval eye and mouth openings. The results of this study showed that newly hatched rainbow boesemani larvae have egg yolks, eyes and mouth. The newly hatched larvae have a yolk volume average of 0.053 mm3. Egg yolks will expire at the time of 2 days old larvae. The formation of the eye, has occurred inside the eggs and newly hatched larvae have an average diameter of eye of 0.459 mm. The newly hatched larvae have a wide mouth opening average of 0.229 mm. An larvae older than 21 days and 30 days has a wide mouth opening average of 0.82 mm and 1.725 mm. Keywords – Rainbow fish Melanotaenia boesemani, larval development, egg yolks, eyes, mouth